Acute Sheehan syndrome following massive postpartum hemorrhage due to vulvar hematoma - Wataru Saito, MD; Kuniaki Ota, MD, PhD; Toshifumi Takahashi, MD, PhD; Mika Sugihara, MD, PhD; Takehiko Matsuyama, MD, PhD; Yoshiaki Ota, MD, PhD; Koichiro Shimoya, MD, PhD (Elsevier, 2024)
Acute Sheehan syndrome appearing within 6 weeks postpartum is a rare form of hypopituitarism caused by postpartum hemorrhage. A 37-year-old Japanese woman experienced a vulvar hematoma after spontaneous labor at 40 weeks gestation, leading to massive postpartum hemorrhage (estimated total blood loss of 3,000 mL). Despite successful cesarean delivery and hematoma drainage, she presented 28 days postpartum with anorexia, fatigue, and hyponatremia after initial recovery. MRI revealed a swollen pituitary gland with subacute hemorrhage, confirming the diagnosis. Hormonal replacement therapy with levothyroxine, hydrocortisone, estrogen, and progesterone was initiated. This is the first reported case of acute Sheehan syndrome following a vulvar hematoma, a condition typically not considered a risk factor for this syndrome. The case highlights the importance of considering rare complications like acute Sheehan syndrome in patients with massive postpartum hemorrhage, even when the pathogenesis is clinically common, such as vulvar hematomas.